The local structure and magnetic correlations in La(Fe1-xMnx)AsO system. (November 2019) - Hacisalihoglu, M.Y.; Paris, E.; Simonelli, L.; Joseph, B.; Provino, A.; Lamura, G.; Martinelli, A.; Manfrinetti, P.; Aquilanti, G.; Ozturk, K.; Dore, P.; Putti, M.; et al.
Abstract: The local structure of La(Fe1- x Mn x )AsO, showing suppression of long-range magnetic order by Mn-substitution, has been studied. Extended X-ray absorption fine structure (EXAFS) measurements at As K-edge and Fe K-edge are used to probe the atomic correlations in the FeAs-layer. We have found that both Fe-As and Fe-Fe bondlengths tend to increase with increasing Mn concentration. The associated mean square relative displacements (MSRD) reveal a gradual increase indicating increased local disorder in the FeAs-layer with Mn content. The results reveal that the FeAs-layer thickness, measured by the As-height ( h As ) from the Fe-Fe plane, is correlated with the Néel temperature. Furthermore, Fe K β X-ray emission spectroscopy (XES) shows a sharp increase in the Fe local magnetic moment with Mn substitution. The importance of the FeAs layer thickness in describing magnetic correlations in La(Fe1− x Mnx )AsO is discussed. Highlights: The effect of Mn substitution on the local structure of La(Fe 1-xMnx)AsO has been studied. Mn substitution induces local disorder in the 1111 structure. Change in the anion height is correlated with the changing TN as a function of Mn substitution. Local Fe moment, measured by XES, increases sharply with Mn concentration. The increase in iron moment may kill superconducting state in doped 1111 system.